1984
DOI: 10.1002/ddr.430040508
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive dysfunction in depression: Difference between depressed and nondepressed elderly patients and differential cognitive effects of nomifensine

Abstract: The main aim of the study was to establish the degree of disturbance of the cognitive functions typical of the elderly depressed patients. The analysis was based on the results of a 4-week, double-blind, placebo-controlled therapeutic study in which the effects and tolerance of the antidepressant nomifensine were tested in a randomized group of 100 patients. Half the patients were depressed and half nondepressed (a priori stratification, HAM-D 2 18). Tests of central nervous arousal, attention, perceptual grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Confirming previous reports [25][26][27][28], this study shows that reversible cognitive impair ment may be present during acute episodes of either major depression or mania. Patients tended to perform worse than controls on conventional immediate and delayed recall tasks and on Benton Lines test, and to show more soft neurological signs than controls [29], On follow-up, these measures (except the Benton) were found to improve.…”
Section: Discussionsupporting
confidence: 77%
“…Confirming previous reports [25][26][27][28], this study shows that reversible cognitive impair ment may be present during acute episodes of either major depression or mania. Patients tended to perform worse than controls on conventional immediate and delayed recall tasks and on Benton Lines test, and to show more soft neurological signs than controls [29], On follow-up, these measures (except the Benton) were found to improve.…”
Section: Discussionsupporting
confidence: 77%
“…In our own studies in depressed elderly patients Siegfried et al, 1984; Siegfried and O'Connolly, 1986;Siegfried, 1989) we found the following:…”
Section: Cognitive Disorders In Old Age Depressionmentioning
confidence: 88%
“…In addition to the GMS-A the Hamilton Depression Scale (HAMD; Hamilton 1967) was used for the assessment of depressive symptoms. Siegfried et al (1984) decided the following classification referring to the 21-item Hamilton Scale: Hamilton Score > 18 = depression; < 7 = no depression.…”
Section: Instrumentsmentioning
confidence: 99%
“…Therefore, the scale points were reduced from 63 to 55 points. The cutoffs of Siegfried et al (1984) were modified: Hamilton score > 16 = depression; < 6 = no depression; between 7 and 15 = no assessment.…”
Section: Instrumentsmentioning
confidence: 99%